Abordagem temática e a introdução de conteúdos de física moderna e contemporânea no ensino médio: uma primeira aproximação - Figueira, Rafael (2014)
The current curricular propositions direct the goals of basic education in the perspective of the student's education as a contemporary citizen who can understand and act in society. Given this configuration, we locate concerns regarding the insertion of latest contents in the curriculum and the development of a more contextualized teaching, through which students can assign a meaning to this knowledge in their lives. Thus, we wondered whether the Thematic Approach could not contribute to the selection and development of content of a more contemporary physics, so they make sense to the students, becoming it effective elements of understanding the world, focusing on its transformation. Given this initial hypothesis, we seek for theses and dissertations in the CAPES' Database of Theses and Dissertations dealing curricular organization from themes and the productions that focus on the reflection on the insertion of Modern and Contemporary Physics (MCP) in basic education. We observed four perspectives for the thematic approach, of which the themes in Freire's perspective and that focusing on Science-Technology- Society relationships (STS) comprise the majority of productions. We identify arguments in justifications for the inclusion of MCP in basic education that are associated with STS dimensions, in most they highlight the importance of this knowledge just by the need to update the curriculum contents and outnumbered we observed the presence of those who focus on the changes in basic education. Seems to us that a thematic approach based on an approximation between Freire's perspective and with a focus on STS relations, can contribute what for the teaching of the content of contemporary physics be articulated to the development of a physics education, aligned with the changes in education in recent decades and that contributes to training which focuses the development of a citizen's and active s posture of student. Accordingly, a possible criterion for the selection of such content would be articulated with the opportunity for students to unveil and understand contradictions related to scientific and technological development, seeking its transformation. So, the development of a thematic investigation could focus on the search for themes that represent environmental implications of scientific and technological development occurred in the last century.